The Russian Orthodox Church during the Great Patriotic War: a review of modern historiography - Evdokimova A. N. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the achievements of modern domestic historiography in the field of relations between the Soviet state and the Russian Orthodox Church during the Great Patriotic War are considered. Among the problems that have been most reflected in regional historiography in recent years are the participation of clergy in charity and the Pskov spiritual mission, the activities of commissioners for the affairs of the Russian Orthodox Church, the transfer of dioceses under the jurisdiction of the Moscow Patriarchate.
Keywords: атеизм; Русская православная церковь; региональная историография; Russian Orthodox Church; atheism; regional historiography; famine in the Volga region